Temperature dependent spectroscopic studies of all-inorganic lead halide perovskites : towards efficient and stable optoelectronic applications - Chen, Xiaoxuan (Nanyang Technological University, 2021)
Lead halide perovskites have attracted enormous interest for their excellent optoelectronic properties like the long carrier diffusion length, high quantum yield, bipolar charge carrier transport, high absorption coefficient, convenient spectral turnability, etc. They are promising candidates for next-generation solar cells, optically pumped lasers, light-emitting diodes, and photodetectors. However, the most widely studied organic-inorganic hybrid lead halide perovskites suffer from instability during shelf storage as well as under operation conditions. All-inorganic perovskites are alternatives that present better stability and competitive performance. With the impetus to delve into this less-explored material system and accelerate the development of all-inorganic lead halide perovskites towards optoelectronics with high efficiency and stability, I have carried out systematic spectroscopic studies with temperature assessment.